Meningkatkan Pelayanan dan Pengunaan Sosial Media sebagai Promosi Camping Ground Berbasis Syari’ah - Nila Pratiwi; Chintya Ones Charli (STMIK Royal, 2024)
This service aims to improve services and use of social media as a sharia-based camping ground promotion in Twin Lakes, Solok Regency. The service method includes initial identification and analysis of the application of social media carried out by sharia-based camping ground managers on the Twin Lakes, preparation of improvement plans in accordance with the characteristics of sharia-based camping grounds through social media, training and assistance for camping ground business managers, as well as evaluation and monitoring to measure the impact of implementing improved services, social media as promotion, it is hoped that the management of the Twin Lakes sharia-based camping ground can improve services and optimize the use of social media. The results of this service can help managers increase interest in visiting, increase visitor attraction, increase promotion of sharia-based camping grounds. Feedback from managers will also be evaluated to assess the success of the service. It is hoped that through this service, Management can have a better understanding of the importance of improving service quality, optimizing effective and efficient social media in promoting sharia-based camping grounds. Apart from that, it is hoped that the management can make a positive contribution to economic growth in Alahan Panjang, Solok district.Keywords : camping ground; promotion; service; social mediaThis service aims to improve services and use of social media as a sharia-based camping ground promotion in Twin Lakes, Solok Regency. The service method includes initial identification and analysis of the application of social media carried out by sharia-based camping ground managers on the Twin Lakes, preparation of improvement plans in accordance with the characteristics of sharia-based camping grounds through social media, training and assistance for camping ground business managers, as well as evaluation and monitoring to measure the impact of implementing improved services, social media as promotion, it is hoped that the management of the Twin Lakes sharia-based camping ground can improve services and optimize the use of social media. The results of this service can help managers increase interest in visiting, increase visitor attraction, increase promotion of sharia-based camping grounds. Feedback from managers will also be evaluated to assess the success of the service. It is hoped that through this service, Management can have a better understanding of the importance of improving service quality, optimizing effective and efficient social media in promoting sharia-based camping grounds. Apart from that, it is hoped that the management can make a positive contribution to economic growth in Alahan Panjang, Solok district. Keywords: camping ground; promotion; service; social media